Implementation of Fairness Principle in Tax Collection for Health Benefits for Outsourced Workers (Study at PT. Pertamina Hulu Sanga Sanga, Kutai Kertanegara Regency, East Kalimantan) - Ghorib Prayitno; Kadek Wiwik Indrayanti (MLJ Merdeka Law Journal, 2021)
Efficiency and effectiveness are important factors for the company. To improve efficiency and effectiveness, the company can perform outsourcing system for labor management. PT. Pertamina Hulu Sanga Sanga has business contracts with three Supporting Service Companies, namely PT. PTC, PT. INJ and PT. IRA as a labor support service company. The three supporting service companies have their own policies in managing their employees who provide personnel services in the Pertamina Hulu Sanga Sanga operational area. One of the differences in the implementation of the policy of supporting service companies among the supporting service companies is the collection of health services tax using ASO (Administrative Services Only) services. This difference became a topic of discussion among outsourcing workers and sparked comparisons between support service companies that use the same health services but one company collects taxes, one does not collect taxes, and the other does not collect taxes but cover as if they were paying premium health insurance. . The research method used is through an empirical legal approach, with an analytical perspective with the object of study covering legal theory, and rules for collecting income taxes, especially health benefits tax for outsourcing workers. The primary data sources in this research are facts in the field and tax laws. Data collection techniques are through field orientation and interviews with outsourced workers and management of outsourcing companies and staff of the Tenggarong Tax Office. The results of the study indicate that the application of the principle of justice in tax collection on outsourcing workers has not been implemented. Legal efforts made by employer companies to regulate the equality of health benefit tax treatment have also not been seen. The existing work contracts are very detailed but still need to be clarified, especially regarding the implementation of health service facilities that can be uniformed for all supporting service companies. In addition, supporting service companies must also be wise in managing business contracts so as not to make policies that harm workers due to misinterpretations in determining whether health insurance is taxed or not.DOI: https://doi.org/10.26905/mlj.v2i1.6238